Semiotic analysis in the lyrics of the song “Untungnya, Hidup Harus Tetap Berjalan” By Bernadya - Hotimah, Emah (Maliki Interdisciplinary Journal, 2025)
This study analyzes the song lyrics Untungnya, Hidup Harus Terus Berjalan by Bernadya using Charles Sanders Peirce’s semiotic theory. The aim is to identify icons, indexes, and symbols in the lyrics and to reveal how these signs construct meaning. The method used is descriptive qualitative, with the lyrics serving as the primary data source. The findings show that the lyrics contain three icons, three indexes, and several symbols that convey resilience, acceptance, and hope. Through these semiotic elements, the song reflects life’s challenges and emphasizes the importance of perseverance and belief in divine plans.